2020
DOI: 10.3390/su12187402
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Calculate the CO2 Emission Reduction at the Coal-Fired Power Plant: CO2 Capture and Utilization Applying Technology of Mineral Carbonation

Abstract: This study introduces a novel methodology to calculate the carbon dioxide (CO2) emission reduction related to residual emissions, calculating the CO2 emission reduction through a 2 MW (40 tCO2/day) carbon capture and utilization (CCU) plant installed at a 500 MW coal-fired power plant in operation, to evaluate the accuracy, maintainability, and reliability of the quantified reduction. By applying the developed methodology to calculate the CO2 emission reduction, the established amount of CO2 reduction in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In the present analysis, the reheat pressure is limited at one-fifth of the main steam pressure in order to avoid exhaust steam qualities below 0.88. In the condenser, the exhaust steam is turned into liquid water 18 . The condensate pump (CP) sends water to the low pressure FWHs 19 .…”
Section: The Reference Steam Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…In the present analysis, the reheat pressure is limited at one-fifth of the main steam pressure in order to avoid exhaust steam qualities below 0.88. In the condenser, the exhaust steam is turned into liquid water 18 . The condensate pump (CP) sends water to the low pressure FWHs 19 .…”
Section: The Reference Steam Cyclementioning
confidence: 99%
“…Advanced ultra-supercritical power plants (A-USC) are expected to enter operation in the next decade for future large-scale CCS implementation. Lee et al [18,19] stressed the importance of developing reliable methodologies for quantifying CO 2 emission reduction through CCS at national basis. Nasirov et al [20] analyzed decarbonization possibilities in developing countries and concluded that wind and solar energy are future of electricity generation, but still 15% of the electricity will be from coal by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, also the few relevant scientific papers discussing economic aspects focus on coal-fired plants [39], and often consider a small nominal net power output related in most cases to pilot plants [40]. Moreover, the technical reports available in the literature usually do not consider the CCS option [41] or they do not include the transportation and storage of CO 2 .…”
Section: Introductionmentioning
confidence: 99%